2021
DOI: 10.3389/fonc.2021.706910
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of ctDNA and bTMB on Immune Checkpoint Inhibitors in Human Cancer

Abstract: BackgroundCirculating tumor DNA (ctDNA) levels and blood tumor mutation burden (bTMB) have a significant impact on the prognosis of tumor patients. However, their prognostic role in immune checkpoint inhibitors (ICIs) in cancer patients is still unclear.MethodsWe used the Review Manager software (version 5.3) to perform a meta-analysis based on the published literature to explore the prognostic value of ctDNA and bTMB in patients receiving immunotherapy. We extracted the hazard ratios (HRs) of progression-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The early response pattern (usually within 8 weeks after treatment initiation) during ICI treatment was recently shown to identify patients with NSCLC responding to therapy, regardless of the stage of the disease. In patients with advanced NSCLC, several groups have recently demonstrated that an early reduction in ctDNA allele frequency, also known as molecular response, was independently associated with longer survival (PFS and overall survival) and a higher response rate [objective response rate (ORR): complete or partial response] in patients with NSCLC treated with durvalumab ( 43 ) and pembrolizumab ± chemotherapy (overall survival: aHR 0.36, 95% CI 0.18–0.7; PFS: aHR 0.33, 95% CI 0.19–0.58) ( 29 , 44 ), as well as other ICIs ( 45 , 46 ). In contrast, an early increase in ctDNA level was associated with increased tumor volume and prolonged duration of treatment in these studies, with landmark time points ranging from within the first 8 weeks to up to 12 weeks on-treatment.…”
Section: Emerging Applications Of Ctdna For Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…The early response pattern (usually within 8 weeks after treatment initiation) during ICI treatment was recently shown to identify patients with NSCLC responding to therapy, regardless of the stage of the disease. In patients with advanced NSCLC, several groups have recently demonstrated that an early reduction in ctDNA allele frequency, also known as molecular response, was independently associated with longer survival (PFS and overall survival) and a higher response rate [objective response rate (ORR): complete or partial response] in patients with NSCLC treated with durvalumab ( 43 ) and pembrolizumab ± chemotherapy (overall survival: aHR 0.36, 95% CI 0.18–0.7; PFS: aHR 0.33, 95% CI 0.19–0.58) ( 29 , 44 ), as well as other ICIs ( 45 , 46 ). In contrast, an early increase in ctDNA level was associated with increased tumor volume and prolonged duration of treatment in these studies, with landmark time points ranging from within the first 8 weeks to up to 12 weeks on-treatment.…”
Section: Emerging Applications Of Ctdna For Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…This is in line with the proposed idea of shifting towards the identification of specific mutations in cfDNA that elicit the generation of highly immunogenic peptides [ 93 ]. As an example, Wei et al performed a meta-analysis of the published literature to evaluate the prognostic value of ctDNA and bTMB in patients receiving ICIs [ 94 ]. Their results showed that, unlike ctDNA clearance, bTMB could not be used independently as a prognostic factor for the response of patients undergoing ICI due to the current limitations of detection technology and a lack of standardization.…”
Section: Circulating Tmb (Btmb)mentioning
confidence: 99%
“…In the same line, other studies proposed the combination of bTMB with other parameters to improve its predictive capacity [ 91 , 92 , 93 , 94 , 95 ]. For instance, a retrospective analysis of POPLAR and OAK studies again supported that bTMB alone may be insufficient to predict ICI outcomes and advised to use it in combination with Maximum Somatic Allele Frequency (MSAF): a parameter that helps to estimate the fraction of tumor cfDNA in peripheral blood samples [ 95 ].…”
Section: Circulating Tmb (Btmb)mentioning
confidence: 99%
See 1 more Smart Citation
“…This liquid biopsy-based cancer genome profiling strategy is now used in daily practice for personalized cancer therapy, although due to its high medical expense, it is only applied for patients with cancer that is refractory to standard chemotherapy. Circulating tumor DNA (ctDNA) has also been reported to predict tumor burden and treatment response, including response to immunotherapy [ 12 ]. However, the potential of cfDNA/ctDNA as an efficacious and/or prognostic biomarker for combination immunotherapy in HCC has never been assessed.…”
Section: Introductionmentioning
confidence: 99%